Concurrent improvement in optical and electrical characteristics by using inverted pyramidal array structures toward efficient Si heterojunction solar cells. (May 2016) - Wang, Hsin-Ping; Li, An-Cheng; Lin, Tzu-Yin; He, Jr-Hau
Abstract: The Si heterojunction (SHJ) solar cell is presently the most popular design in the crystalline Si ( c -Si) photovoltaics due to the high open-circuit voltages ( V OC ). Photon management by surface structuring techniques to control the light entering the devices is critical for boosting cell efficiency although it usually comes with the V OC loss caused by severe surface recombination. For the first time, the periodic inverted pyramid (IP) structure fabricated by photolithography and anisotropic etching processes was employed for SHJ solar cells, demonstrating concurrent improvement in optical and electrical characteristics (i.e., short-circuit current density ( J SC ) and V OC ). Periodic IP structures show superior light-harvesting properties as most of the incident rays bounce three times on the walls of the IPs but only twice between conventional random upright pyramids (UPs). The high minority carrier lifetime of the IP structures after a -Si:H passivation results in an enhanced V OC by 28 mV, showing improved carrier collection efficiency due to the superior passivation of the IP structure over the random UP structures. The superior antireflective (AR) ability and passivation results demonstrate that the IP structure has the potential to replace conventional UP structures to further boost the efficiency in solar cell applications. Graphical abstract: Highlights: Periodic inverted pyramid (IP) structures employed for Si heterojunction (SHJ). Improved carrier collection efficiency by the superior passivation of IP structures. SHJ cells with the optimized IP structure achieving the efficiency of 14.6.